(untitled) (Mongolian Journal of Arts and Culture, 2025)
This study aims to identify the reasons for the declining enrollment in journalism programs in Mongolia over the past decade, as well as the decreasing interest among students in pursuing careers in journalism. In addition to analyzing enrollment data from the past five years, the study conducted online surveys in 2020 and 2023 to assess students’ perceptions of the journalism profession. A total of 426 students from journalism departments across several universities participated in the survey. with low salaries and intense time pressures, are key factors discouraging students from entering the field. Furthermore, social media-based harassment and public criticism of journalists have emerged as major challenges for journalism students. Despite the availability of jobs in the sector, unfavorable working conditions have contributed to a shortage of human resources. Journalism schools are facing a dual challenge. On the one hand, the digital transformation is rapidly displacing traditional media outlets, leading to a noticeable decline in student enrollment. On the other hand, there is growing demand in the job market for graduates who are equipped with a wide range of multimedia skills and are capable of producing journalism across multiple platforms. As a result, journalism programs are under pressure to modernize their curricula and prepare students for the demands of a convergent media environment. Монголын сэтгүүл зүйн боловсрол: Өөрчлөлт Хураангуй: Энэ судалгаа нь Монгол Улсад сүүлийн арван жилд сэтгүүлч мэргэжлээр элсэлт буурсан, энэ чиглэлээр суралцаж байгаа оюутнуудын мэргэжлээрээ ажиллах сонирхол буурсан шалтгааныг илрүүлэх зорилготой юм. Сэтгүүлчээр суралцаж байгаа оюутнуудын сүүлийн таван жил дэх тоон мэдээлэлд шинжилгээ хийхээс гадна сэтгүүлч бэлтгэдэг их, дээд сургуулийн давхардсан тоогоор 426 оюутнаас онлайнаар 2020, 2023 онд мэргэжлийн үнэлэмжийн судалгааг асуулгын аргаар авч дүгнэлт гаргалаа. Сэтгүүлч мэргэжлийн нэр хүнд унаж, цалин багатай, цагийн дарамт ихтэй ажил гэж ойлгогдох болсон нь гол шалтгаан байв. Үүнээс гадна нийгмийн зүгээс сэтгүүлчдэд ирэх сошиал хүчирхийлэл сэтгүүлчээр суралцагч оюутнуудад томоохон сорилт болжээ. Иймд ажлын байр хангалттай байгаа ч хөдөлмөрийн нөхцөлөөс хамаараад хүний нөөцийн хомсдолд орсон салбар болж байна. Харин сэтгүүл зүйн сургуулиуд хоёр талдаа бэрхшээлтэй тулгарч байна. Нэг талаараа дижитал хувьсгал уламжлалт мэдээллийн хэрэгслийг хүчээр шахаж байгаа тул оюутны тоо мэдэгдэхүйц буурч байна. Нөгөө талаар, сэтгүүл зүйн сургуулиудад оюутнууд өргөн хүрээний мултимедиа ур чадварыг эзэмшүүлэхийг шаардаж, нэгэн зэрэг олон платформд агуулга хүргэх шинэ хэлбэрийн сэтгүүл зүйн чиглэлээр мэргэшсэн төгсөгчдийг ажилд авах эрэлт улам бүр нэмэгдэж байна. Түлхүүр үгс: сэтгүүл зүйн дээд боловсрол, хэрэгцээ шаардлага, сорилт боломж, мэргэжлийн үнэлэмж